Sifat-Sifat Fungsi yang Terintegral Mcshane dalam Ruang Euclide Berdimensi N untuk Fungsi-Fungsi Bernilai Banach - Kristayulita Kristayulita (Universitas Islam Negeri (UIN) Mataram, 2012)
This paper contains McShane integral banach values function the Euclidean space R^n. We study some properties of McShane integrable functions from the Euclidean space R^n into Banach space